ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Vivi Adeyani Tandean (Universitas Bunda Mulia, 2017)
The financial report is one of the important instruments that support the sustainability of a company and is useful when presented with accurate and timely. Audit delay is the time difference between the date of the financial report and the date of the audit opinion of the financial report that indicate the length of time to complete the audit by the auditor. The study aims to measure the factors which affect audit delay. They are auditor’s reputation, auditor’s opinion, company size, solvability, operation loss and profit, return on asset, earning per share and ownership of company. The sample in this study was 54 manufactured companies on Indonesia Stock Exchange in 2010 – 2012 were taken by purposive sampling metod. The data analysis uses multiple linear regression. The result of the study shows that factor of auditor’s opinion and ownership of company have significant influence towards audit delay partially. On the other hand that factor of auditor’s reputation, company size, solvability, operational loss and profit, return on asset and earning per share do not have any influence towards audit delay partially. While simultaneously, all factor in auditor’s reputation, auditor’s opinion, company size, solvability, operation loss and profit, return on asset, earning per share and ownership of companyinfluence towards audit delay. Keywords : audit delay, auditor, ownership of company